METABOLIC BENEFITS OF ADDING SODIUM GLUCOSE CO-TRANSPORTER-2 INHIBITORS IN REAL-WORLD SETTINGS, A TERTIARY CENTRE EXPERIENCE - Guan, Goh Kian; Wei, Scott Chung Chin; Amin, Md Syazwan Md (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Sodium-glucose co-transporter-2 inhibitors (SGLT2i) have revolutionized the landscape of type 2 diabetes (T2D). Ministry of Health facilities in Malaysia manage approximately 1.6 million individuals with diabetes. Due to the high risk for cardiovascular disease, SGLT2i are indicated for these patients. METHODOLOGY This study looks at metabolic benefits for subjects started on SGLT2 inhibitors in tertiary hospital settings. This retrospective cohort study included patients with T2D who started on SGLT2i (empagliflozin or dapagliflozin) from 2018 to 2024. Data on age, weight change, HbA1c and total daily dose of insulin (TDD) were obtained for one year from initiation of SGLT2i. RESULTS Total sample recruited was 100. Mean age was 57.2 years. Six subjects were on dapagliflozin, and 94 subjects were on empagliflozin. Mean baseline weight was 80.6 kg, HbA1c was 9.19% and insulin TDD was 45.46 units. At one year, mean weight reduction was 2.54 kg (95%CI [-3.556,-1.528]), P = <0.001. Mean HbA1c change was -0.02% (95%CI [-0.730, -0.695]), P = 0.961. Similarly, a slight reduction of insulin TDD by 2.6 units was observed at one year (95%CI [-6.51, -1.28], P = 0.184). CONCLUSION Significant weight reduction was observed at 1 year, similar to other studies. Most patients reported the greatest weight loss during the first three months, possibly due to the diuretic effect of SGLT2i. Though HbA1c did not show a significant reduction in our cohort, the insulin TDD was slightly lower at 12 months, which may translate to a long-term reduction in healthcare costs. Limitations include fewer patients on dapagliflozin as this medication was only recently available in our facilities. Future studies should include a follow-up period with data on cardiovascular and renal outcomes.